(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
search aims to find out the extent to which the child (4-5 years old) is able to express the personal emotions under the current circumstances and to propose a program according to the levels of learning through play activities to develop the ability of expressing the child’s personal emotions directed to kindergarten teachers. To answer the research questions, the descriptive analytical was adopted, through a scale to measure the ability of Expressing the child’s personal emotions (Aldarghaly, 2013) and the research sample consisted of (104) boys and girls from Rural Damascus. The researcher then concluded the following important results: The ability to express the emotion of joy among the sample was average, while the ability to express the emotion of fear, sadness and anger was low among the sample of the research, and the researchers proposed a program according to the levels of learning through play activities to develop the child’s skills in expressing his personal emotions.